The Effect of Flubendazole on Adhesion and Migration in SW480 and SW620 Colon Cancer Cells - Hanušová, Veronika; Skálová, Lenka; Králová, Věra; Matoušková, Petra (Anti-cancer agents in medicinal chemistry, 2018)
BACKGROUND: Colon cancer is the most common type of gastrointestinal cancer. Despite advances during the last two decades, the efficacy of colorectal cancer treatment is still insufficient and new anticancer agents are necessary. METHODS: In our study, colon cancer cells derived from a primary tumor (SW480) and lymph node metastasis (SW620) from the same patient were used and compared. The effect of flubendazole (FLU) on cell adhesion and migration was monitored using the x-CELLigence Real-Time Cell Analysis system. Expressions of molecules involved in adhesion and migration were analyzed using RT-PCR and western blot. Furthermore, RNA silencing of nuclear factor-κB in SW620 cells was used to determine the involvement of the NF-κB p65 regulation pathway in FLU action. RESULTS: FLU significantly suppressed the adhesion of SW480 cells and reduced the expression of adhesion markers (ICAM-1, αE-catenin; β-catenin; integrin α5 and β1). Moreover, a significant anti-migratory potential of FLU was manifested in the SW620 cells. In addition, FLU suppressed the phosphorylation of NF-κB p65 and potentiated the suppression of several metastatic markers (ICAM-1, EpCAM, integrin α5, β1, α-tubulin) caused by NF-κB p65 silencing. CONCLUSION: FLU has a significant anti-migratory effect in intestinal cancer cell SW480 and its lymph node metastatic cells SW620. FLU decreases the expression of some proteins involved in metastatic processes and inhibits activation of NF-κB p65.
Keywords: Drug Screening Assays, Antitumor; RNA silencing; Humans; Tumor Cells, Cultured; nádory tračníku; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Colonic Neoplasms; Dose-Response Relationship, Drug; Antineoplastic Agents; metastasis; Cell Adhesion; Colon cancer; lidé; proliferace buněk; molekulární struktura; nádorové buňky kultivované; Molecular Structure; migration.; pohyb buněk; mebendazol; Cell Proliferation; Mebendazole; Cell Movement; screeningové testy protinádorových léčiv; protinádorové látky; vztah mezi dávkou a účinkem léčiva; buněčná adheze; flubendazole; adhesion